PS1 -125 Assessment of Function and Quality of Life in a Phase II Multi-Institutional Clinical Trial of Fractionated Simultaneous In-Field Boost Radiotherapy for Patients with 1-2 Brain Metastases. (18th October 2016) - Bauman, G; Yartsev, S; Roberge, D; MacRae, R.; Roa, W; Panet-Raymond, V; Masucci, L; Yaremko, B; D'Souza, D.; Palma, D.; Sexton, T.; Yu, E.; et al.
Abstract : We examined functional outcomes and quality of life of whole brain radiotherapy (WBRT) with integrated fractionated stereotactic radiotherapy boost (FSRT) for brain metastases treatment. Methods Eighty seven people with 1-3 brain metastases were enrolled on this Phase II trial of WBRT (30Gy/10)+simultaneous FSRT, (60Gy/10). Results Mean (Min-Max) baseline KPS, Mini Mental Status Exam (MMSE) and FACT-BR quality of life were 83 (70-100), 28 (21-30) and 143 (98-153). Lower baseline MMSE (but not KPS or FACT-Br) was associated with worse survival after adjusting for age, number of metastases, primary and extra-cranial disease status. Crude rates of deterioration (>10 points decrease from baseline for KPS and FACT-Br, MMSE fall to<27) ranged from 26-38% for KPS, 32-59% for FACT-Br and 0-16%for MMSE depending on the time-point assessed with higher rates generally noted at earlier time points (<6months post-treatment). Using a linear mixed models analysis, significant declines from baseline were noted for KPS and FACT-Br (largest effects at 6 weeks to 3 months) with no significant change in MMSE. Conclusions The effects on function and quality of life of this integrated treatment of WBRT+simultaneous FSRT were similar to other published series combining WBRT+SRS.